Development of Numeracy Learning Media to Improve Critical Thinking Skills of Sixth-Grade Students in Elementary Schools in Central Jakarta - Permatasari, Putri; Susanto, Ahmad; Sofian Hadi, Muhamad (Global Action and Education for Society, 2026)
This study aims to develop numeracy learning media in the form of a numeracy board and examine its effectiveness in improving the critical thinking skills of sixth-grade elementary school students in Central Jakarta. The research was motivated by the low achievement in numeracy and critical thinking, as indicated by the 2024 education report and interviews with teachers, which showed that mathematics was one of the least favored subjects due to conventional teaching methods. The research method employed was Research and Development (R&D) with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The research subjects were 56 sixth-grade students from SDN Gondangdia 05 and SDN Cikini 01 Pagi, Menteng District. Research instruments included critical thinking skill tests, student and teacher questionnaires, and observation sheets. Validation results showed excellent feasibility ratings, with 92% from material experts, 96% from design experts, and 97% from language experts, while teachers rated 94% and students 97%, indicating that the media was practical and engaging in the learning process. The pretest average score was 50.54, while the posttest average increased to 86.05, with an improvement of 35.51%. The t-test showed a significant difference with p < 0.05, and the N-Gain score of 0.72 was categorized as high, indicating that the numeracy board was effective in enhancing critical thinking skills. Therefore, the numeracy board is proven to be feasible, practical, and effective as interactive mathematics learning media that supports the development of higher-order thinking skills.